Petasis/Diels–Alder/Cyclization Cascade Reactions for the Generation of Scaffolds with Multiple Stereogenic Centers and Orthogonal Handles for Library Production. Issue 36 (15th June 2018) - Flagstad, Thomas; Azevedo, Carlos M. G.; Min, Geanna; Willaume, Anthony; Morgentin, Rémy; Nielsen, Thomas E.; Clausen, Mads H.
Abstract : A new effective strategy for the synthesis of sp 3 ‐rich small molecules for library production is presented. The key steps to generate complexity involve a Petasis three‐component reaction followed by an intramolecular Diels–Alder and cyclization to generate a densely enriched tricyclic or tetracyclic scaffolds with 3–4 stereocenters and three handles for decoration. The strategy was used for the production of 143 molecules for the European Lead Factory. Abstract : The synthesis of tricyclic and tetracyclic scaffolds with three to four stereocenters, high fraction of sp 3 carbon atoms (Fsp 3 ), low molecular weight and three handles for decoration is described. The key steps to generate complexity are a Petasis reaction followed by an intramolecular Diels–Alder and cyclization cascade. The strategy was used to produce 143 molecules for the European Lead Factory public compound collection.